Construção de uma narrativa cinematográfica não-linear: o roteiro e filme "21 Gramas" - Silva, Túlio César Gama e (2008)
The dissertation consists of investigating alternative forms of dramatic and narratives structures for the development of cinematographic script. Trying to detect distinct models of narrative construction, the research has as main object the study on the script of the film 21 Grams (2003), of the Mexican scriptwriter Guillermo Arriaga. At a first moment, a comparison of the script and the film will be made, following the methodology of the Genetic Criticism to understand the structural approach of the work. The analysis will have as support the studies of specialized authors in audiovisuals scripts as Flávio de Campos, David Bordwell and Jean-Claude Carrière; however, the effort of the research will be to unmask the properties and the limits of the processes of creation of cinematographic narrative and to extend the dimension of the possibilities of creative development on cinema script. 21 Grams is presented as example of a possible "shunting line" of the dramatical standardization, since it shows a narrative form of nonlinear time and multi-protagonists. The fragmentation, at the beginning, seems to divergir basic laws of classic narrative, as the unity law and continuous progression law. The narrative of 21 Grams, thus, brings as attractive its own narrative form, where the way to tell a story is so attractive as much the content of story